Estudio y análisis del Conocimiento, Actitud y Práctica (CAP) en los usuarios de las tarjetas de crédito en la ciudad de Loja, periodo 2015 – 2018 - Morocho Armijos, Darwin Efrain (2019)
This thesis work entitled "Study and analysis of knowledge, attitude and practice (CAP) in the users of credit cards in the city of Loja, period 2015 - 2018", It arises from the need to present an analysis of the behavior of the media in the city of Loja, to conduct an exploratory study of credit cards as a means of payment, history and the use they have given in recent years since They have increased considerably, among the elderly, not only of upper class, media and media, as well as in the number of cards issued, their total balances, level of indebtedness and delinquency that have reflected the Credit card issued by financial institutions in the years from 2015 to 2018. The results of a Knowledge, Attitude and Practice (CAP) survey have been analyzed, in order to determine the degree of knowledge and attitudes in the use of credit cards by determining two analysis variables in cardholders; in their financial culture about credit cards, the use they give them and their importance. The inductive and deductive methods were used since these allow to measure the impact that originates in the cardholders, as well as the use they give and the importance of the credit cards. According to the main results obtained, it is concluded that there is a bad culture in the handling of the cards as well as a lack of knowledge of the functions that it has, requesting the majority of the distant population that there are courses of everything that entails having in their possession a card of credit. They use it daily as a means of payment when they do not have enough cash to purchase products or services such as: food, clothing, health, education, etc.